Evaluation of Hemoglobin and Creatinine Levels in Chronic Renal Failure Patients Undergoing Hemodialysis Therapy - Prodyanatasari, Arshy; Purnadianti, Mely (Utan Kayu Publishing, 2024)
Chronic Renal Failure (CKD) is a disease that occurs when the kidneys fail to maintain the body's fluid composition. Hemodialysis is one of the therapies to replace deteriorating kidney function. Deteriorating kidney function conditions cause the ability of erythropoietin to be disrupted and anemia occurs, so checking hemoglobin levels is useful to control the patient's hemoglobin levels and creatinine examination to detect the severity of kidney function disorders. This study aims to determine the relationship of hemodialysis therapy with hemoglobin and creatinine levels in CKD patients at Baptist Hospital, Kediri City. This study is important to obtain information and provide education to patients regarding the significant effect of hemodialysis therapy for chronic renal failure patients so that chronic renal failure patients are motivated and disciplined to carry out hemodialysis therapy according to a set schedule. The design of this study was a cross-sectional survey with independent variables being hemodialysis therapy in patients with chronic renal failure and dependent variables being hemoglobin and creatinine levels. 30 respondents were using the quota sampling method. The results of this study were the average examination results of hemoglobin levels of 9.0 g/dL and creatinine of 4.45 mg/dL. Based on the Pearson Correlation test, the correlation coefficient (r) is 0.369, and the p-value = (0.045) > alpha = 0.05 (5%), thus H1 is accepted. The relationship between hemoglobin and creatinine levels in patients with chronic renal failure undergoing therapy hemodialysis at Baptist Hospital in Kediri City.